Vertical and lateral distribution of Foraminifera and Ostracoda in the East Frisian Wadden Sea – developing a transfer function for relative sea-level change - Scheder, Juliane; Frenzel, Peter; Bungenstock, Friederike; Engel, Max; Brückner, Helmut; Pint, Anna (Geologica Belgica, 2019)
"In light of rising sea levels and increased storm surge hazards, detailed information on relative sea-level (RSL) histories and local controlling mechanisms is required to support future projections and to better prepare for future coastal-protection challenges. This study contributes to deciphering Holocene RSL changes at the German North Sea coast in high resolution by developing a transfer function for RSL change. Recent associations of Foraminifera and Ostracoda from low intertidal to supratidal settings of the barrier island of Spiekeroog in combination with environmental parameters (granulometry, C/N, total organic carbon, salinity) were investigated and quantified in elevation steps of 15 cm in order to generate a first transfer function (TF) of Holocene RSL change. In a future step, the TF can be applied to the stratigraphic record. Our data show a clear vertical zonation of foraminifer and ostracod taxa between the middle salt marsh and the tidal flat with very few individuals in the sand flat area, suggesting removal by the tidal current or poor preservation. Multivariate statistics identify the elevation, corresponding to the inundation frequency, as main driving factor. The smallest vertical error (49 cm) is associated with an entirely new approach of combining Foraminifera and Ostracoda for a TF. Advantages of the TF over classical RSL indicators such as basal and intercalated peats – beside the relatively narrow indicative meaning – include the possible application to a wide range of intertidal facies and that the resulting RSL curve does not depend on compaction-prone peats." (Abstract)